TV 3.0: An Overview - Chaubet, Allan Seiti Sassaqui (2024)
A new Digital Terrestrial Television Broadcasting (DTTB) system, called Television (TV) 3.0, is being developed in Brazil and is expected to be on air by 2025 under the commercial name DTV+. It started with a Call for Proposals (CfP) for its systems components, for which organizations worldwide have submitted candidate technologies. After two testing and evaluation phases, the technologies for all layers were selected, the TV 3.0 architecture was completely defined, and the standards were written. It consists of modern Modulation and Code (MODCOD) techniques, mandatory transmission and reception in Multiple-Input Multiple-Output (MIMO) with cross-polarized antennas, an app-oriented interface, an Internet-based Transport Layer (TL), and state-of-the-art efficient coding for audio, video, and captions. This set of technologies will allow for several new use cases that change the user experience with TV, such as Geographically Segmented Broadcasting (GSB), targeted advertising, sensory effects, and interactivity. This paper reviews the phases already concluded for the TV 3.0 project and presents its potentialities and the current developments at its final stage.